How Factors Involved in the Resolution of Crystal-Induced Inflammation Target IL-1β - Oliviero, Francesca; Scanu, Anna (Frontiers in Pharmacology, 2017)
One of the main clinical features characterizing crystal-induced inflammation is its spontaneous resolution. The aim of this review is to outline the various factors involved in the self-limiting course of crystal-induced inflammation focusing on their effect on IL-1β production. Endogenous molecules that are induced or locally recruited by the process itself, inhibitory proteins naturally present in the joint and exogenous dietary factors are discussed. Aside from the classical well known molecules involved in the resolution of crystal-induced acute attack such as TGFß, IL-10, IL-1Ra, and lipoproteins, particular attention is paid to recently uncovered mechanisms such as the aggregation of neutrophil extracellular traps, the release of ectosomes from neutrophil surface, and alpha-1-anti-trypsin-mediated IL-1 inhibition.